Finite Element Analysis of the Effects of Bolt Condition on Bolted Rail Joint Stresses. Issue 1 (2016) - Zhu, Kaijun; Edwards, J. Riley; Qian, Yu; Andrawes, Bassem
The rail joint is typically considered to be one of the weakest locations in the track superstructure. Defects and failures—including bolt hole cracks, head–web cracking or separation, broken or missing bolts, and joint bar cracking—have been found to start at rail joints and the area surrounding these joints. The initiation and propagation of these defects are primarily attributable to the discontinuities of both geometric and mechanical properties in the rail joint area and the high-impact loads induced by the discontinuities. Loosened or missing rail joint bolts can decrease the overall stiffness at the joint. A loosened rail joint can also accelerate certain types of defects, such as cracking around the bolt hole and the head–web fillet area (the upper fillet area) close to the rail end. These cracks present both economical and safety concerns as they can significantly reduce the service life of the rail or joint bar and even lead to breaks in the rail. However, the effect of bolt condition on stress propagation around bolted rail joints is not thoroughly understood. This study investigated the effects of bolt loading and missing-bolt configurations on the stress distribution at the bolt hole and the upper fillet area under static loading conditions. A comprehensive parametric analysis was performed with finite element modeling. Preliminary results showed that when bolt loading increased, the rail vertical displacement and stresses on the rail upper fillet decreased, but the stresses on bolt holes increased. The two center bolts, which were closest to the rail end, were the most sensitive bolts in terms of variation in stresses in response to changes in bolting and torqueing.